Biological control of Diaphorina citri with the predatory mite Amblyseius herbicolus - Kalile, Milena Oliveira (2020)
Pesticide use is becoming increasingly limited worldwide because of problems with the environment, food safety and their negative effects on beneficial animals such as pollinators and natural enemies. In addition, it can cause pest resistance, starting a vicious cycle of increases of doses that do not solve the pest problem but increase it. Biological control is a key alternative to pesticide use to control crop pests, because it is safe, often effective and environmental-friendly. Generalist predators are promising biological control agents because their populations can be established in the crop with alternative food earlier in the season, which makes the system more resilient to pest invasions. Predatory mites, many of which are generalists, are among the best-selling natural enemies to control crop pests. Nevertheless, much remains to be investigated about natural enemies controlling insect vectors and the possible reduction of pathogen spread. For example, there is still no natural enemy commercialized to control the Asian citrus psyllid Diaphorina citri, vector of the bacteria that cause Huanglongbing or Greening, the most devastating citrus disease in the world, also causing considerable economic losses in Brazil. Biological control with parasitoids of D. citri is not effective enough and mass rearing of this natural enemy is laborious. I studied Amblyseius herbicolus, a generalist predatory mite, which can potentially control Bemisia tabaci and Polyphagotarsonemus latus, and occurs on citrus and orange jasmine plants in Minas Gerais, Brazil. My aim was to evaluate the potential of this predator to control D. citri. Additionally, I explored methods to enable mass rearing of this predator for future field releases and commercialization. I show that A. herbicolus is potentially effective to control D. citri in laboratory tests and on orange jasmine plants. Besides, A. herbicolus can develop and reproduce on the storage mite Thyreophagus cracentiseta, which will facilitate mass rearing and releases of this predator in the field. Keywords: Greening. Citrus. Asian citrus psyllid. Generalist predators. Mass rearing.